In-depth analysis of the performance of hybrid desiccant cooling system incorporated with an electric heat pump - Hwang, Won-Baek; Choi, Sun; Lee, Dae-Young (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Aiming for improvement of the cooling performance, the hybrid desiccant cooling system (HDCS) is investigated and compared with a reference desiccant cooling system (RDCS). By replacing a sensible wheel of the RDCS with a heat pump, the HDCS is expected to increase the energy efficiency as well as to improve the system compactness. The cooling cycle is simulated and its results are compared with those of the RDCS. The analysis showed that specific cooling power of the HDCS increases from that of RDCS, promising the miniaturization of the system. Also, COP of HDCS was found to overtake the COP of RDCS in a particular range of heat pump capacity. For analysis of total energy consumption, a new parameter, R, the ratio of the primary energy factor of electrical energy to the primary energy factor of thermal energy was introduced. In the range of R (=5-10) such as from the CHP plants, the optimal heat pump capacity was estimated when the heat pump occupies 30-40% of the total cooling output of the HDCS. With the optimal configuration, the total energy consumption of HDCS reduces by 20-30% and the cooling capacity of HDCS increases by 40-60%, compared to RDCS. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: AIR-CONDITIONING SYSTEM; ENERGY PERFORMANCE; WHEEL; HOT; REFRIGERATION; OPTIMIZATION